Tyrosine sulfation of CCR5 N-terminal peptide by tyrosylprotein sulfotransferases 1 and 2 follows a discrete pattern and temporal sequence - Seibert, Christoph (National Academy of Sciences, 2002)
The CC-chemokine receptor 5 (CCR5) is the major coreceptor for the entry of macrophage-tropic (R5) HIV-1 strains into target cells. Posttranslational sulfation of tyrosine residues in the N-terminal tail of CCR5 is critical for high affinity interaction of the receptor with the HIV-1 envelope glycoprotein gp120 in complex with CD4. Here, we focused on defining precisely the sulfation pattern of the N terminus of CCR5 by using recombinant human tyrosylprotein sulfotransferases TPST-1 and TPST-2 to modify a synthetic peptide that corresponds to amino acids 2–18 of the receptor (CCR5 2–18). Analysis of the reaction products was made with a combination of reversed-phase HPLC, proteolytic cleavage, and matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry (MALDI-TOF MS). We found that CCR5 2–18 is sulfated by both TPST isoenzymes leading to a final product with four sulfotyrosine residues. Sulfates were added stepwise to the peptide producing specific intermediates with one, two, or three sulfotyrosines. The pattern of sulfation in these intermediates suggests that Tyr-14 and Tyr-15 are sulfated first, followed by Tyr-10, and finally Tyr-3. These results represent a detailed analysis of the multiple sulfation reaction of a peptide substrate by TPSTs and provide a structural basis for understanding the role of tyrosine sulfation of CCR5 in HIV-1 coreceptor and chemokine receptor function.